Intikhab-e-Kalam Mir Anis - Mir Anis, Babar Ali; Edited and introduced by Raza Kazmi, Muhammad (Karachi Oxford University Press, 2015)
This book contains a selection from the marasi (elegiac epics) of Mir Anis, hailed as the greatest exponent of this form, as well as one of the greatest poets of the Urdu language. The theme is the Tragedy of Karbala 680 A.D. and Mir Anis has presented his elegies in long narrative poems with descriptions of the ground, single combats, and general engagement, the death of the protagonist followed by lamentation. The marasi are also noted for being pure in their diction and exemplary in their idiom. All British historians of Urdu literature are united in according him a very high stature in Urdu Literature.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam Mir Anis